ANTINATAL DIETARY CARE - A REVIEW ARTICLE - Jain, Ankita Rajendra; S. T., Vishala (International Journal of Research -GRANTHAALAYAH, 2017)
As per Ayurvedic literature each month of pregnancy has its unique requirement which is very important for every pregnant woman. There is detail description regarding pathya-apathya for garbhini. The pregnancy diet ideally should be light, nutritious, easily digestable and rich in proteins, minerals, and vitamins. Selection of right kind of pregnancy diet can decide the mental and physical health of child so it becomes important to pay extra attention for what u should eat and what u should not. Diet guidelines described under garbhiniparicharya is ideal protocol for pregnant women.